Evaluation of Telenomus remus (Hymenoptera: Platygastridae) as a biocontrol agent of Spodoptera litura (Lepidoptera: Noctuidae) based on two-sex life table and functional response analyses - Zhen Shen; Li-Hui Liu; Lian-Sheng Zang; Tie-Jun Deng; Zhen-Bao Luo; Jun-Yi Gao; Liang-De Tang (CABI Agriculture and Bioscience)
Abstract Background Telenomus remus Nixon is an important egg parasitoid of Spodoptera spp. pests and, as such, has potential as a biological control agent. Spodoptera litura (Fabricius) is a significant pest of many economically important crops worldwide. This study was conducted to evaluate the demographic parameters and functional response of T. remus on the S. litura eggs. Results T. remus can lay 186.90 eggs/female in the lifetime, adult preoviposition period was 0 days, total preoviposition period was 10.03 days, and the ratio of female and male offspring was 0.495 and 0.421, respectively. In addition, most females emerged from 24 h-old eggs, whereas most males emerged from 48 h-old eggs. The intrinsic rate of increase, finite rate of increase, net reproductive rate, mean generation time, and population doubling time were 0.3506 d–1 1.4199 d–1 92.45 offspring/individua, 12.91 days and 1.98 days, respectively. The net killing rate of T. remus on S. litura was 101.49 eggs/female, indicating the high capacity of T. remus to parasitize S. litura eggs. Moreover, the higher the egg density, the higher the parasitism rate by female T. remus, although there was a trend of parasitism stabilization at an egg density of 100, indicating a type II functional response curve for this parasitoid. Conclusion Overall, these findings suggest that T. remus can be efficiently reared on S. litura eggs and shows potential as biocontrol agent for this economically important pest species.